(untitled) (Jurnal ForestrIndo, 2025)
Land use is one of the factors that affects the rainfall-runoff transformation of the watershed. This study aims to analyze land use changes and the differences of the Soil Conservation Service–Curve Number model calculations to predict rainfall-runoff transformation in the Cimanceuri Watershed. Land use changes are analyzed using geoprocessing-intersect Land Use Maps of the Ministry of Environment and Forestry, 2018 and 2023. The rainfall-runoff transformation was analyzed using four different calculation methods of the Soil Conservation Service–Curve Number model, namely Q1, Q2, Q3, and Q4. The results showed that the area of Forests and Plantations decreased by 99.2% and 17.9%, respectively, while the area of Mixed Agricultural Land and Settlements increased by 16.4% and 19.1%, respectively. The average curve number increased from 73.0 to 73.7. Surface runoff decreased from 114.0 to 112.9 mm/month. The average monthly rainfall in 2018 and 2023 was 184 and 182 mm/month, respectively. The surface runoff/rainfall ratio is fixed at 62%. Four calculation methods result in different runoff estimates. The Q1 calculation method resulted in the best spatial results among the four methods. This study confirms that the reduction of the area of Forests and Plantations does not necessarily increase the runoff of a watershed, depending on the occurrence of rainfall.